2017
DOI: 10.1038/s41598-017-08679-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity among four healthcare-associated institutes in Taiwan

Abstract: Indoor microbial communities have important implications for human health, especially in health-care institutes (HCIs). The factors that determine the diversity and composition of microbiomes in a built environment remain unclear. Herein, we used 16S rRNA amplicon sequencing to investigate the relationships between building attributes and surface bacterial communities among four HCIs located in three buildings. We examined the surface bacterial communities and environmental parameters in the buildings supplied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…Sampling sites around a bed in each ICUs and OTs were chosen based on the frequency with which the surfaces were touched. Sterile swabs were moistened in Brain Heart Infusion (BHI) and then, were used to swab (i) commonly touched medical equipment including beds, monitors, OR-light, linens, ventilators, oxygen supply, anesthesia machine, suction buttons and Laparoscopy (ii) workstation, including keyboards, computer mice; (iii) environments including floors, wall and corridors; (iv) Lobby (furniture) including chair, table, lockers and trowels; (v) Sinks; (vi) hospital textiles including bed linen based on methods described previously [17][18][19][20].…”
Section: Surfaces Samplingmentioning
confidence: 99%
“…Sampling sites around a bed in each ICUs and OTs were chosen based on the frequency with which the surfaces were touched. Sterile swabs were moistened in Brain Heart Infusion (BHI) and then, were used to swab (i) commonly touched medical equipment including beds, monitors, OR-light, linens, ventilators, oxygen supply, anesthesia machine, suction buttons and Laparoscopy (ii) workstation, including keyboards, computer mice; (iii) environments including floors, wall and corridors; (iv) Lobby (furniture) including chair, table, lockers and trowels; (v) Sinks; (vi) hospital textiles including bed linen based on methods described previously [17][18][19][20].…”
Section: Surfaces Samplingmentioning
confidence: 99%
“…An exhaustive study prospectively determined the microbiome of the wards in a newly completed hospital, finding a significant increase in human skin microbiota after hospital opening [9]. Other work has identified the durability of specific pathogens on hospital surfaces despite disinfection [10], which demonstrated that surface microbiomes vary depending on extent and diversity of human contact [11] and revealed the homogeneity of core microbiota across healthcare units [12]. These studies largely focused on hospital wards outside of the ICUs.…”
Section: Introductionmentioning
confidence: 99%
“…The development of metagenomics has made it possible to profile the entire community structure, characterizing individual microbes without the need for isolation, and represents a high-throughput and scalable method for surveying the hospital environment microbiome 19 . This capability has been leveraged in the form of 16S rRNA sequencing to study bacterial diversity, particularly in intensive care units (ICU), in several early studies [20][21][22][23] . In a landmark study in 2017, Lax et al used this approach to extensively characterize microbial ecology, colonization and succession patterns in a newly built hospital environment (a subset with shotgun metagenomics) 24 .…”
Section: Introductionmentioning
confidence: 99%